2013
DOI: 10.1179/2046023613y.0000000032
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of arginase-I expression in formalin-fixed lung and other tissues

Abstract: Arginases are a family of enzymes that convert L-arginine to L-ornithine and urea. Alterations in expression of the isoform arginase-I are increasingly recognized in lung diseases such as asthma and cystic fibrosis. To define expression of murine arginase-I in formalin-fixed tissues, including lung, an immunohistochemical protocol was validated in murine liver; a tissue that has distinct zonal arginase-I expression making it a useful control. In the lung, arginase-I immunostaining was observed in airway surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…It has been reported that both Arg-I and Arg-II are present in skin. Arg-I is mainly expressed in bulbs of anagen follicles along with lower expression in the adnexal sebaceous glands and surface epithelium (Hochstedler et al, 2013 ), whereas Arg-II is mainly expressed in skin keratinocytes and fibroblasts (Debats et al, 2009 ). Our current work confirms the observation that Arg-II is expressed in keratinocytes and in fibroblasts (co-localized with α-SMA positive cells) but also in α-SMA negative cells, probably resident immune cells (Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that both Arg-I and Arg-II are present in skin. Arg-I is mainly expressed in bulbs of anagen follicles along with lower expression in the adnexal sebaceous glands and surface epithelium (Hochstedler et al, 2013 ), whereas Arg-II is mainly expressed in skin keratinocytes and fibroblasts (Debats et al, 2009 ). Our current work confirms the observation that Arg-II is expressed in keratinocytes and in fibroblasts (co-localized with α-SMA positive cells) but also in α-SMA negative cells, probably resident immune cells (Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…There are two distinct isoenzymes of mammalian arginase: arginase‐1 (ARG1) and ARG2. ARG1, which plays a critical role in urea biogenesis, is highly expressed in the liver, but not in skin (Hochstedler, Leidinger, Maher‐Sturm, Gibson‐Corley, & Meyerholz, ). On the other hand, ARG2 is expressed in diverse extrahepatic tissues lacking a complete urea cycle, including skin keratinocytes and fibroblasts (Debats et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Outside the liver, Arg1 is expressed in macrophages [6, 7, 34], where it has been reported to be a marker of an alternatively activated macrophage phenotype [9, 11, 35, 36]. To determine whether the increase in Arg1 observed 14 days post-bleomycin injury was due to an increase in the number of alternatively activated macrophages in the lungs, we analyzed macrophage differentiation by flow cytometry using standard markers for myeloid cell activation.…”
Section: Resultsmentioning
confidence: 99%